2011
DOI: 10.1186/1471-2148-11-300
|View full text |Cite
|
Sign up to set email alerts
|

What are the consequences of combining nuclear and mitochondrial data for phylogenetic analysis? Lessons from Plethodonsalamanders and 13 other vertebrate clades

Abstract: BackgroundThe use of mitochondrial DNA data in phylogenetics is controversial, yet studies that combine mitochondrial and nuclear DNA data (mtDNA and nucDNA) to estimate phylogeny are common, especially in vertebrates. Surprisingly, the consequences of combining these data types are largely unexplored, and many fundamental questions remain unaddressed in the literature. For example, how much do trees from mtDNA and nucDNA differ? How are topological conflicts between these data types typically resolved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 94 publications
4
54
0
Order By: Relevance
“…Despite incongruences between the mitochondrial and nuclear gene trees, the concatenated gene tree and the species tree reconstructed with multilocus data strongly supported the same topology separating Nesticella into three geographically well-defined clades: A, B, and C. The combined gene tree was dominated by nuclear data, which was not unexpected since Fisher-Reid and Wiens [49] suggested that nuclear genes had lower levels of homoplasy than mitochondrial genes. The relatively rapidly evolving mitochondrial genes supported the monophyly of Clades A plus B, which probably resulted from ancestral polymorphisms and lineage sorting [49].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Despite incongruences between the mitochondrial and nuclear gene trees, the concatenated gene tree and the species tree reconstructed with multilocus data strongly supported the same topology separating Nesticella into three geographically well-defined clades: A, B, and C. The combined gene tree was dominated by nuclear data, which was not unexpected since Fisher-Reid and Wiens [49] suggested that nuclear genes had lower levels of homoplasy than mitochondrial genes. The relatively rapidly evolving mitochondrial genes supported the monophyly of Clades A plus B, which probably resulted from ancestral polymorphisms and lineage sorting [49].…”
Section: Discussionmentioning
confidence: 64%
“…The relatively rapidly evolving mitochondrial genes supported the monophyly of Clades A plus B, which probably resulted from ancestral polymorphisms and lineage sorting [49]. Overall, our data was sufficient to resolve the phylogenetic relationship among the taxa.…”
Section: Discussionmentioning
confidence: 71%
“…In other cases, conflicts with our results might reflect the impact of our sampling fewer nuclear genes and a correspondingly increased influence of mitochondrial data. Mitochondrial genes have relatively fast evolutionary rates (potentially exacerbating the impacts of long branches), and their phylogenetic resolution for a particular node may also reflect introgression or incomplete lineage sorting rather than the species phylogeny (review in [196]). Many taxa in the matrix are represented only by mitochondrial data, and highly variable mitochondrial genes might also overcome the influence of less variable nuclear genes in combined analyses (although this scenario does not seem to be common [196]).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the lack of differentiation at a single marker is insufficient to extrapolate to the entire genome, especially in view of the different inheritance in the mitochondrial and nuclear genomes [74, 75]. A previous molecular study used only mitochondrial evidence and found no consistent genetic differentiation associated with each ecotype [29] but failed to demonstrate genetic homogeneity in the nuclear genome.…”
Section: Discussionmentioning
confidence: 99%